2020
DOI: 10.1002/cnma.202000009
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Coating Improves the Signal‐to‐Noise Ratio of Iron Oxide Nanoparticles in Magnetic Particle Imaging (MPI)

Abstract: Magnetic particle imaging is an emerging tomographic method used for evaluation of the spatial distribution of iron-oxide nanoparticles. In this work, the effect of the polymer coating on the response of particles was studied. Particles with covalently crosslinked coating showed improved signal and image resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…8 . It should be noted that the SNR of a signal produced by magnetic nanoparticles is markedly affected by the volume fraction f V actually present in the target; 76 as a consequence, when f V is low (≲0.01) such as in some MPI/MPS applications, the temperature-sensitive MSV is expected to provide more reliable experimental results.…”
Section: Comparison Between the Proposed Techniquesmentioning
confidence: 99%
“…8 . It should be noted that the SNR of a signal produced by magnetic nanoparticles is markedly affected by the volume fraction f V actually present in the target; 76 as a consequence, when f V is low (≲0.01) such as in some MPI/MPS applications, the temperature-sensitive MSV is expected to provide more reliable experimental results.…”
Section: Comparison Between the Proposed Techniquesmentioning
confidence: 99%
“…In one study, Horvat et al reported the positive impact of preparing SPIONs with cross-linked over noncrosslinked polymeric coatings on performance in MPI. 246 The cross-linked single-core SPIONs, of average core size 18 nm, termed PF127DAPG, displayed a superior SNR, and consequently higher spatial resolution than their uncross-linked equivalents, PF127. Resulting from this, an iron quantity of 5.3 μg was required in PF127 SPIONs to produce the same spatial resolution values as 1.3 μg of iron in PF127DAPG SPIONs.…”
Section: Effect Of Spions On Spatial Resolution and Sensitivity In Mpimentioning
confidence: 99%
“…Currently, no such SPIONs have been approved for clinical treatment, yet it has already been demonstrated that enhanced MPI performance can be realised through specific SPION design, with improvements in for example, MPI spatial resolution and sensitivity. 14,16,219,243,245,246 Notably, further optimisation of the SPIONs for spatial resolution can be traded-off for lower MPI gradients, lowering the overall cost of MPI implementation and easing the scale-up of hardware to human size. 230 With different cores, coatings, and the potential conjugation of targeting and therapeutic moieties, it is anticipated that SPIONs will be designed for many different applications and disease processes.…”
Section: Clinical Translationmentioning
confidence: 99%
“…The main requirements of MNPs for MPI imaging are: (i) superparamagnetic behavior, (ii) the capacity to be magnetically saturated, and (iii) the ability to exhibit a nonlinear magnetization curve [ 115 ]. In general, SPIONs with superior crystallinity features and larger and monodispersed sizes (≥20 nm), presenting higher magnetic moments and high-quality images, make the best MPI tracers [ 18 , 115 , 120 , 121 ].…”
Section: Magnetic Nanoparticle-based Non-traditional Multimodal Imaging For Cancer Diagnosismentioning
confidence: 99%